IDENTIFIKASI BAKTERI STAPHYLOCOCCUS AUREUS PADA SUSU SAPI PERAH YANG DI PERJUALBELIKAN DI PETERNAKAN ASAM KUMBANG KECAMATAN MEDAN SELAYANG - Eka Margareta Sinaga (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2016)
Milk is a drink that is mandatory for dikomsumsi by the community, especially for children, therefore, the milk must be free from bacterial contamination patongen. Dairymilk is a type of milk that is contaminated by bacteria susceptible patongen is Staphylococcus aureus, through tools that used less clean, dirty environment, handworkers, etc. The purpose of this research is to find out whether or not there areStaphylococcus aureus in milk of dairy cows in the perjual subdistrict of dipeternakan Acid Beetles traded Medan Selayang. This research uses descriptive method. The Media's use are bouillon, serves to nourish the growth of microbes that were about tobe isolated. After breeding in media boillon done staining gram gram staining, results from samples found three terkontaminas cocci gram positive bacteria in samples of S2, S3, S4. Then do breeding on a selective medium, while selective media used are MSA, serves to microbial so selecting one type of microbe will grow. After breeding in theMSA media done staining gram. Catalase test is then conducted on a sample of S2, S3,S4. the results of the test of catalase is positive. then do a test koagulase to determine the bacteria staphylococcus aureus. Koagulase results from a sample of S2 is positive.of the seven samples of dairy milk which is examined, there is one sample thatcontaminated the bacteria staphylococcus aureus.